2021
DOI: 10.3389/fpubh.2021.753443
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Portable Electrocardiogram for Screening Cardiovascular Diseases at a Primary Health Center in Ahmedabad District, India

Abstract: Background: District Health Authority in Ahmedabad, Gujarat has introduced Project Lifeline, 12-lead portable ECG devices across all primary health centers (PHC) in the district to screen cardiac abnormalities among high-risk and symptomatic adults for providing primary management and proper timely referral. The prime purpose of the study was to assess the cost-effectiveness of portable ECG for the screening of cardiovascular diseases (CVD) among high-risk and symptomatic adults at the PHC in Ahmedabad, Gujara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Os dados disponíveis consolidaram-no como uma ferramenta válida e custo-efetiva para melhorar a acurácia diagnóstica e terapêutica em locais onde faltam especialistas, além de promover cuidados de saúde para populações com acesso subótimo. 9,19 Nossos dados reforçam a utilidade diagnóstica do tele-ECG de uma perspectiva mais ampla, com previsão ideal de DC grave detectada pelo ecocardiograma de rastreamento, mesmo após ajuste para variáveis clínicas relevantes.…”
Section: Fraga Et Al Ferramentas Combinadas De Telecardiologia Na Ate...unclassified
“…Os dados disponíveis consolidaram-no como uma ferramenta válida e custo-efetiva para melhorar a acurácia diagnóstica e terapêutica em locais onde faltam especialistas, além de promover cuidados de saúde para populações com acesso subótimo. 9,19 Nossos dados reforçam a utilidade diagnóstica do tele-ECG de uma perspectiva mais ampla, com previsão ideal de DC grave detectada pelo ecocardiograma de rastreamento, mesmo após ajuste para variáveis clínicas relevantes.…”
Section: Fraga Et Al Ferramentas Combinadas De Telecardiologia Na Ate...unclassified
“…A cost-effectiveness analysis done in Ahmedabad, a city in the same state, analyzing the monetary benefits of using a portable ECG for the screening of CVDs among high-risk and symptomatic patients in PHCs showed promising results with 2.9 life years saved at a cost-effectiveness ratio of 2,299.06 INR per life-year saved [7]. The use of portable ECGs at PHCs could justifiably fill the gap uncovered by our need assessment as it makes up only a small proportion of the State Health Expenditure.…”
Section: Contextualizing Findingsmentioning
confidence: 99%
“…The availability of an ECG machine under Project Lifeline in Ahmedabad, Gujarat showed that effective screening in a high-risk population saved 2.90 life years at a cost of 31.07 USD (approximately 2,299.06 INR) per life-year saved, which is below the willingness to pay threshold. Along with the need to increase the availability of such devices, it is also essential to train primary care physicians such that they are better able to interpret ECG readings [7]. For a majority of the underprivileged population, PHCs still remain the first point of contact for health-related care and thus accurate diagnosis and management of all cardiovascular diseases is fundamental in ensuring better prognostic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other instruments like 12-lead portable ECG devices for the screening of cardiovascular diseases in Ahemdabad found that screening at PHC by ECG saves 2.9 lives per year at an incremental cost of 89.97 USD, yielding a cost-effectiveness ratio of 31.07 USD, so the facility to screen cardiac abnormality at PHC level is highly recommended for risk adults and symptomatic cases ( 17 ). It coincides with the US preventive services task force for screening for prediabetes and type 2 diabetes at ages 35–70 years in a primary setting, which has a moderate net benefit.…”
Section: Introductionmentioning
confidence: 99%